Investigation of experimental endovascular air embolisms using a new model for the generation and detection of highly calibrated micro air bubbles - Schaefer, Tabea; Greive, Svenja; Heiland, Sabine; Kramer, Martin; Bendszus, Martin; Vollherbst, Dominik (Journal of endovascular therapy, 2022)
Background:Air embolism (AE), especially when affecting the brain, is an underrated and potentially life-threatening complication in various endovascular interventions. This study aims to investigate experimental AEs using a new model to generate micro air bubbles (MAB), to assess the impact of a catheter on these MAB, and to demonstrate the applicability of this model in vivo.Materials and Methods:Micro air bubbles were created using a system based on microfluidic channels. The MAB were detected and analyzed automatically. Micro air bubbles, with a target size of 85 µm, were generated and injected through a microcatheter. The MAB diameters proximal and distal to the catheter were assessed and compared. In a subsequent in vivo application, 2000 MAB were injected into the aorta (at the aortic valve) and into the common carotid artery (CCA) of a rat, respectively, using a microcatheter, resembling AE occurring during cardiovascular interventions.Results:Micro air bubbles with a highly calibrated size could be successfully generated (median: 85.5 µm, SD 1.9 µm). After passage of the microcatheter, the MAB were similar in diameter (median: 86.6 µm) but at a lower number (60.1% of the injected MAB) and a substantially higher scattering of diameters (SD 29.6 µm). In vivo injection of MAB into the aorta resulted in cerebral microinfarctions in both hemispheres, whereas injection into the CCA caused exclusively ipsilateral microinfarctions.Conclusion:Using this new AE model, MAB can be generated precisely and reproducibly, resulting in cerebral microinfarctions. This model is feasible for further studies on the pathophysiology and prevention of AE in cardiovascular procedures.